Ridge augmentation and root coverage using acellular dermal matrix: A case report - Kavitha Jayavel (Dental Research Journal, 2010)
Excessive alveolar bone resorption is commonly found when teeth are extracted. This is a problem in anterior part of mouth because it will result in an unaesthetic pontic on a narrow hollowed out alveolar ridge. Yet, another problem is gingival recession and root exposure in adjacent teeth which represent a therapeutic problem to the clinician. Use of acellular dermal matrix graft is an appropriate solution to obtain root coverage in areas with localized or generalized soft tissue recessions, particularly if the recessions create aesthetic concern or root sensitivity or shallow root caries lesions. This case report describes a surgical technique using acellular dermal matrix graft on a class III ridge defect and Millers grade II gingival recessions. There was a gain in both bucco-lingual and apico-coronal dimensions of the ridge, in both height and width directions, when compared to baseline and after 3 months. Recession was also covered compared to the baseline condition.